Preparation method for electrochemically preparing high-compactness electron transport type electrode film on non-conductive substrate and application of high-compactness electron transport type electrode film
By preparing PBFDO films by electrochemical polymerization and reducing doping treatment on non-conductive substrates, the problem of insufficient film density and stability is solved, and an n-type conductive polymer film with high density, high stability and high conductivity is achieved, which is suitable for cathodes of organic electronic devices.
Patent Information
- Application Number
- CN202411991964.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing n-type conductive polymer PBFDO films have insufficient density and stability due to irregular arrangement of rigid chains during film formation, which affects their application in organic electronic devices.
High-density electron transport electrode films are prepared by electrochemical polymerization and reducing doping treatment on non-conductive substrates. The internal voids of the film are filled with electrochemical polymerization and improved flatness, and then the conductivity is further enhanced by reducing doping.
It significantly improves the density and stability of the PBFDO film, improves its conductivity, is suitable for the cathode of flexible electronic devices and organic electronic devices, and has good electron transport capabilities.
Smart Images

Figure CN119852029A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of conductive polymer film preparation and organic optoelectronic technology, and mainly to a method for preparing a high-density electron transport electrode film on a non-conductive substrate by electrochemistry and its application. Background Art
[0002] With the popularity and growing demand for electronic products such as smartphones, tablets, and displays, the demand for high-performance, low-cost, and flexible electrode materials is also increasing. Traditional transparent electrode materials such as indium tin oxide (ITO) have many disadvantages, such as complex preparation processes, limited overall resources, and difficulty in achieving flexibility. Conductive polymers, as a potential alternative, are expected to overcome these problems, attracting many research institutions and companies to invest in research and development.
[0003] Conductive polymers with conjugated main chains as their main feature can allow carriers to move through them, thus having excellent conductive properties and being able to achieve performance comparable to or even exceeding that of traditional materials. In addition, conductive polymers also have solution processability, so that electrodes suitable for various electronic products can be prepared by printing and other methods, and low-cost large-area preparation can be achieved. Secondly, conductive polymers inherit the excellent mechanical properties of traditional organic materials and have good flexibility. Flexible electrodes can be customized by bending, stretching, etc. according to product requirements, and are suitable for curved display screens, flexible electronic devices and other fields. In addition, the preparation process of conductive polymer materials is relatively simple, and process improvements are expected to reduce product production costs and improve market competitiveness.
[0004] However, the application of conductive polymers in electrodes still faces some challenges. First of all, the current mainstream conductive polymers are p-type conductive polymers dominated by hole carriers, such as the commonly used poly(3,4-ethylenedioxythiophene) (PEDOT), so they are usually used as anodes in organic electronic devices to collect / transmit holes. However, the conductivity and stability of n-type conductive polymer materials dominated by electron carriers still need to be improved, and the material formulation and preparation process need to be further optimized. In addition, the durability and environmental adaptability of conductive polymer materials also need further research and improvement to ensure the stability and durability of the products in practical applications. In 2022, the n-type conductive polymer poly(3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione) (PBFDO) with both ultra-high conductivity and high stability was reported (Nature, 2022, 611, 271-277), which promoted the application of n-type conductive polymers in organic electronic devices and attracted more and more attention. However, PBFDO is a rigid linear polymer molecule. During the film-forming process of the PBFDO solution prepared by chemical polymerization reaction, the irregular arrangement of its rigid chains will lead to large gaps inside the film. The conductivity and stability of large-area films are greatly affected by the processing technology, which causes certain difficulties in application.
[0005] Therefore, improving the compactness and stability of PBFDO films is of great significance for promoting the large-scale application of n-type conducting polymers, especially their application as electron transport electrodes in organic electronic devices and even flexible electronic devices.
[0006] In summary, it is necessary to develop a new technical solution to solve the defects and shortcomings in the existing technology. Summary of the invention
[0007] The present invention provides a preparation method of a high-density electron-transporting electrode film prepared by electrochemistry on a non-conductive substrate and its application. The high-density electron-transporting electrode film prepared by electrochemistry on a non-conductive substrate has a more dense and smooth surface morphology. The electrode film can be used as a cathode in an organic electronic device, has the advantages of high electrical conductivity, simple processing and preparation, and suitability for flexible devices, and has significant economic value and social benefits.
[0008] An object of the present invention is to provide a method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical preparation, the method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical preparation comprises the following steps:
[0009] S1, placing an oxidant, 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione and / or poly(3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione) on a substrate to obtain a conductive film substrate layer;
[0010] S2, mixing 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione, a solvent, and an acid anhydride to obtain an electrolyte;
[0011] S3, adding the conductive film substrate layer into an electrolyte, and performing electrochemical polymerization using a three-electrode system to obtain an electrochemically polymerized film I.
[0012] Furthermore, in step S1, the solvent of the oxidant is an alcohol and / or ester solvent.
[0013] Furthermore, in step S1, the solvent of the 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione is dimethyl sulfoxide.
[0014] Furthermore, the method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical preparation may further include the following steps:
[0015] S4. Using a three-electrode system, the electrochemically polymerized film I is subjected to reduction doping treatment to obtain a final conductive film II.
[0016] Furthermore, in step S1, the oxidant, 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione and / or poly(3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione) are disposed on the substrate:
[0017] The oxidant and 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione are placed on the surface of the substrate, and heated and dried. After repeating n times, a conductive film substrate layer is obtained.
[0018] or
[0019] The poly (3,7-dihydrobenzo [1,2-b: 4,5-b'] difuran-2,6-dione) is disposed on the surface of the substrate, and after heating and drying, a conductive film substrate layer is obtained;
[0020] The n is 1-20.
[0021] Furthermore, the substrate includes but is not limited to one or more of glass, quartz, polyimide, and polyurethane.
[0022] Furthermore, the setting on the surface of the substrate adopts an immersion method or a coating method.
[0023] Furthermore, in step S2, the solvent is selected from one or more polar aprotic solvents.
[0024] Furthermore, the polar aprotic solvent includes, but is not limited to, dimethyl sulfoxide, acetonitrile, tetrahydrofuran, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and hexamethylphosphoric triamide.
[0025] Furthermore, in step S2, the acid anhydride includes but is not limited to acetic anhydride, propionic anhydride, butyric anhydride, benzoic anhydride, and maleic anhydride.
[0026] Furthermore, a suitable electrolyte may be added to the electrolyte to improve the conductivity of the electrolyte, and the electrolyte includes but is not limited to non-alkaline electrolytes such as tetrabutylammonium hexafluorophosphonate, sodium chloride, and lithium bis(trifluoromethanesulfonyl)imide.
[0027] Furthermore, in step S3, in the three-electrode system, the conductive film substrate layer obtained in S1 is used as the working electrode, the platinum wire is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode.
[0028] Furthermore, in step S3, the electrochemical polymerization is carried out by constant current method, constant voltage method or cyclic voltammetry, and the oxidation potential is -1.5 to 3.0 V relative to the reference electrode or the current density is 0.001 to 500 mA / cm 2 , the polymerization time is 20 to 200 minutes or 20 to 2000 cycles.
[0029] Furthermore, the cyclic voltammetry method can simultaneously perform electrochemical polymerization and reduction doping treatment.
[0030] Furthermore, in step S4, the reduction doping is carried out by a constant current method or a constant voltage method, and the reduction potential is -1.5 to 0.5 V relative to the reference electrode or the reduction current density is 0.001 to 100 mA / cm 2 , time is 1 to 10 minutes.
[0031] Furthermore, in step S4, in the three-electrode system, the electrochemical polymerization treated film I is used as the working electrode, the platinum wire is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode.
[0032] Another object of the present invention is to provide the application of the above-mentioned high-density electron transport electrode film prepared by electrochemistry on a non-conductive substrate in organic electronic devices.
[0033] Furthermore, the organic electronic devices include flexible electronics, organic solar cells, organic photodetectors, organic light-emitting devices, etc.
[0034] The present invention has the following beneficial effects:
[0035] (1) The present invention uses an electrochemical polymerization method to prepare and modify a conductive film in a low-cost, non-toxic, and low-pollution manner without introducing other impurities. The electrochemical polymerization method can fill the porous PBFDO film originally obtained by chemical polymerization or deposition, making it flatter and tighter, and further doping the electrochemically polymerized PBFDO film through further electrochemical reduction, further improving the conductivity, and finally obtaining an n-type conductive polymer film with high compactness, high stability, and high conductivity.
[0036] (2) The present invention uses an independently designed and prepared electrolyte for electrochemical polymerization and reduction doping, which is a brand-new technology in the field. Different electrolyte systems can be customized according to different application scenarios. It can meet the customization of various parameters such as BFDO monomer concentration, electrolyte type, solvent type, electrochemical method, polymerization / reduction doping voltage, polymerization / reduction doping time, etc. during the electrochemical polymerization process, so that it can be applied to different scenarios and has wide practicality.
[0037] (3) Since the compactness and stability of the film can be significantly improved, the method of the present invention has significant effects in the application of organic electronic devices, including organic solar cells, organic photodetectors, organic light-emitting devices, and other fields. The prepared film, as the cathode of the organic electronic device, has a compact and smooth surface morphology and good electron transmission ability, and is simple to process and prepare, and is suitable for flexible devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 SEM images of the thin films prepared in Preparation Examples 1, 3, and 5 are shown.
[0039] Figure 2 SEM images of the M1-1, M3-1, M5-1, M7-1, and M9-1 films prepared in Examples 1 to 9 are shown.
[0040] Figure 3 The JV curves of organic solar cells based on the thin films prepared in Preparation Examples 1 to 6 are shown;
[0041] in,
[0042] Figure 3 (a) is the JV curve of the organic solar cell based on the thin films prepared in Preparation Examples 1 to 3,
[0043] Figure 3 (b) is the JV curve of the organic solar cell based on the thin films prepared in Preparation Examples 4 to 6.
[0044] Figure 4 The JV curves of organic solar cells based on the doped thin films prepared in Examples 1 to 9 are shown;
[0045] in,
[0046] Figure 4 (a) is the JV curve of the organic solar cell based on the doped thin film prepared in Examples 1 to 3,
[0047] Figure 4 (b) is the JV curve of the organic solar cell based on the doped thin film prepared in Examples 4 to 6,
[0048] Figure 4 (c) is the JV curve of the organic solar cell based on the doped thin film prepared in Examples 7 to 9.
[0049] Figure 5 The dark current density (J) of the organic photodetector based on the thin films prepared in Preparation Examples 1 to 6 is shown. d ) and external quantum efficiency (EQE) curves;
[0050] in,
[0051] Figure 5 (a) is the dark current density (J) of the organic photodetector based on the thin films prepared in Preparation Examples 1 to 3 d )curve,
[0052] Figure 5 (b) is an external quantum efficiency (EQE) curve of an organic photodetector based on the thin films prepared in Preparation Examples 1 to 3,
[0053] Figure 5 (c) is the dark current density (J) of the organic photodetector based on the thin films prepared in Preparation Examples 4 to 6 d )curve,
[0054] Figure 5 (d) is the external quantum efficiency (EQE) curve of the organic photodetector based on the thin films prepared in Preparation Examples 4 to 6.
[0055] Figure 6 The dark current density (J) of the organic photodetector based on the doped thin films prepared in Examples 1 to 9 is shown. d ) and external quantum efficiency (EQE) curves;
[0056] in,
[0057] Figure 6 (a) is the dark current density (J) of the organic photodetector after doping of the thin film prepared in Examples 1 to 3 d )curve,
[0058] Figure 6 (b) is an external quantum efficiency (EQE) curve of an organic photodetector based on the doped thin film prepared in Examples 1 to 3,
[0059] Figure 6 (c) is the dark current density (J) of the organic photodetector based on the doped thin films prepared in Examples 4 to 6 d )curve,
[0060] Figure 6 (d) is an external quantum efficiency (EQE) curve of an organic photodetector based on the doped thin film prepared in Examples 4 to 6,
[0061] Figure 6 (e) is the dark current density (J) of the organic photodetector based on the doped thin films prepared in Examples 7 to 9 d )curve,
[0062] Figure 6 (f) is the external quantum efficiency (EQE) curve of the organic photodetector based on the doped thin films prepared in Examples 7 to 9. DETAILED DESCRIPTION
[0063] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0064] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0065] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers indicating, for example, the amounts of ingredients used in the specification and claims should be understood to be modified in all cases by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values that vary depending on the desired properties to be obtained by the present invention.
[0066] Reference for the synthesis of PBFDO: Tang Haoran, et al. A solution-processed n-type conducting polymer with ultrahigh conductivity. Nature, 2022, 611, 271~277.
[0067] Preparation Example 1
[0068] A method for obtaining a conductive film substrate layer by chemical polymerization comprises the following steps:
[0069] S1. Evenly coat 20 μL of 2 mg / mL PBFDO solution on a 1.0 cm×1.0 cm glass sheet, and vacuum dry at 80° C. for 30 min to obtain a PBFDO film D1, ie, a deposited conductive film base layer D1.
[0070] Preparation Example 2
[0071] A method for obtaining a conductive film substrate layer by in-situ chemical polymerization comprises the following steps:
[0072] S1. Dissolve 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione monomer (BFDO) in dimethyl sulfoxide (DMSO) to obtain a solution with a BFDO monomer concentration of 10 mg / mL; dissolve selenium dioxide in isopropanol to obtain an oxidant solution with a concentration of 2 mg / mL, evenly coat 20 μL of the oxidant solution on a 1.0 cm×1.0 cm glass sheet, dry at 80°C for 15 min, then evenly coat 20 μL of the BFDO monomer solution on the above glass sheet, dry at 80°C in vacuum for 15 min, and after 2 cycles of coating, obtain a conductive film base layer D2.
[0073] Preparation Example 3
[0074] A method for obtaining a conductive film substrate layer by in-situ chemical polymerization comprises the following steps:
[0075] S1. Dissolve BFDO monomer in DMSO to obtain a solution with a BFDO monomer concentration of 10 mg / mL; dissolve copper acetate in ethanol to obtain an oxidant solution with a concentration of 5 mg / mL, soak a 1.0 cm×1.0 cm glass sheet in the oxidant solution and the BFDO monomer solution in turn, dry at 80°C in a vacuum for 20 min, and after 4 cycles of soaking, obtain a conductive film base layer D3.
[0076] Preparation Example 4
[0077] A method for obtaining a conductive film substrate layer on a flexible substrate by in-situ chemical polymerization comprises the following steps:
[0078] S1. Dissolve BFDO monomer in DMSO to obtain a solution with a BFDO monomer concentration of 10 mg / mL; dissolve selenium dioxide in isopropanol to obtain an oxidant solution with a concentration of 2 mg / mL, and immerse a 1.0 cm×1.0 cm flexible PI substrate in the oxidant solution and the BFDO monomer solution in turn. After each immersion, dry it at 80°C in a vacuum for 20 minutes. After 4 cycles of immersion, a conductive film substrate layer D4 is obtained.
[0079] Preparation Example 5
[0080] A method for chemically immersing a conductive film substrate comprises the following steps:
[0081] The conductive film substrate D1 obtained in Preparation Example 1 was immersed in a DMSO solution of 10 mg / mL BFDO monomer, and 2% of the total volume of acetic anhydride was added. After immersion at room temperature for 60 minutes, a chemically immersed conductive film substrate D5 was obtained.
[0082] Preparation Example 6
[0083] A method for chemically immersing a conductive film substrate comprises the following steps:
[0084] The conductive film substrate D2 obtained in Preparation Example 2 was immersed in a DMSO solution of 10 mg / mL BFDO monomer, and 2% of the total volume of acetic anhydride was added. After immersion for 60 minutes, a chemically immersed conductive film substrate D6 was obtained.
[0085] Example 1
[0086] A method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical preparation, comprising the following steps:
[0087] S2, dissolving BFDO monomer in a mixed solvent of DMSO and acetic anhydride (the volume ratio of DMSO to acetic anhydride is 95:5) to obtain a solution with a BFDO monomer concentration of 10 mg / mL, adding 0.1 mol / L tetrabutylammonium hexafluorophosphonate to obtain an electrolyte;
[0088] S3, adding the conductive film substrate D1 into the electrolyte, using D1 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, using a three-electrode system and a constant voltage method to perform electrochemical polymerization, with the potential relative to the reference electrode being 1.4 V, and the time being 60 min. After the polymerization reaction, the working electrode is taken out, and dried at 80° C. in a vacuum for 20 min to obtain an electrochemically polymerized film M1;
[0089] S4. Add the electrochemically polymerized film M1 into the electrolyte, use M1 as the working electrode, platinum wire as the counter electrode, saturated calomel electrode as the reference electrode, and adopt a three-electrode system and constant voltage method to carry out reduction doping treatment. The potential is -0.5 V relative to the reference electrode, and the time is 2 minutes. After the reaction, take out the working electrode, dry it at 80°C in vacuum for 20 minutes to obtain the final conductive film M1-1.
[0090] Example 2
[0091] A method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical preparation, comprising the following steps:
[0092] S2, dissolving BFDO monomer in a mixed solvent of DMSO and propionic anhydride (the volume ratio of DMSO to propionic anhydride is 95:5) to obtain a solution with a BFDO monomer concentration of 10 mg / mL, adding 0.1 mol / L tetrabutylammonium hexafluorophosphonate to obtain an electrolyte;
[0093] S3, adding the conductive film substrate D4 into the electrolyte, using D4 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, using a three-electrode system and a constant voltage method to perform electrochemical polymerization, the potential relative to the reference electrode is 2.0 V, the time is 60 min, after the polymerization reaction, the working electrode is taken out, and vacuum dried at 80°C for 30 min to obtain an electrochemically polymerized film M2;
[0094] S4. Add the electrochemically polymerized film M2 into the electrolyte, use M2 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, and use a three-electrode system and constant voltage method to carry out reduction doping treatment. The potential is -0.5 V relative to the reference electrode, and the time is 3 minutes. After the reaction, take out the working electrode, and dry it at 80°C in vacuum for 20 minutes to obtain the final conductive film M2-1.
[0095] Example 3
[0096] A method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical preparation, comprising the following steps:
[0097] S2, dissolving the BFDO monomer in a mixed solvent of DMSO and butyric anhydride (the volume ratio of DMSO to butyric anhydride is 95:5) to obtain an electrolyte with a BFDO monomer concentration of 10 mg / mL;
[0098] S3, adding the conductive film substrate D2 into the electrolyte, using D2 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, using a three-electrode system and a constant voltage method to perform electrochemical polymerization, the potential relative to the reference electrode is 2.0 V, the time is 60 min, after the polymerization reaction, the working electrode is taken out, and vacuum dried at 80° C. for 60 min to obtain an electrochemically polymerized film M3;
[0099] S4. Add the electrochemically polymerized film M3 into the electrolyte, use M3 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, and use a three-electrode system and constant voltage method to carry out reduction doping treatment. The potential is -0.4 V relative to the reference electrode, and the time is 2 minutes. After the reaction, take out the working electrode, and dry it at 80°C in vacuum for 20 minutes to obtain the final conductive film M3-1.
[0100] Example 4
[0101] A method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical preparation, comprising the following steps:
[0102] S2, dissolving BFDO monomer in a mixed solution of acetonitrile, DMSO and propionic anhydride (the volume ratio of acetonitrile, DMSO and propionic anhydride is 90:5:5) to obtain an electrolyte with a BFDO monomer concentration of 10 mg / mL;
[0103] S3, adding the conductive film substrate D2 into the electrolyte, using D2 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, using a three-electrode system and a constant voltage method to perform electrochemical polymerization, the potential relative to the reference electrode is 2.5 V, the time is 50 min, after the polymerization reaction, the working electrode is taken out, and vacuum dried at 80° C. for 20 min to obtain an electrochemically polymerized film M4;
[0104] S4. Add the electrochemically polymerized film M4 into the electrolyte, use M4 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, and use a three-electrode system and constant voltage method to carry out reduction doping treatment. The potential is -0.5 V relative to the reference electrode, and the time is 2 minutes. After the reaction, take out the working electrode, and dry it at 80°C in vacuum for 20 minutes to obtain the final conductive film M4-1.
[0105] Example 5
[0106] A method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical preparation, comprising the following steps:
[0107] S2, dissolving BFDO monomer in a mixed solution of 1,4-dioxane, DMSO and propionic anhydride (the volume ratio of 1,4-dioxane, DMSO and propionic anhydride is 8:1:1) to obtain an electrolyte with a BFDO monomer concentration of 10 mg / mL;
[0108] S3, adding the conductive film substrate D2 into the electrolyte, using D2 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, using a three-electrode system and a constant voltage method to perform electrochemical polymerization, the potential relative to the reference electrode is 2.0 V, the time is 50 min, after the polymerization reaction, the working electrode is taken out, and vacuum dried at 80°C for 30 min to obtain an electrochemically polymerized film M5;
[0109] S4. Add the electrochemically polymerized film M5 into the electrolyte, use M5 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, and use a three-electrode system and constant voltage method to carry out reduction doping treatment. The potential is -0.5 V relative to the reference electrode, and the time is 2 minutes. After the reaction, take out the working electrode, and dry it at 80°C in vacuum for 20 minutes to obtain the final conductive film M5-1.
[0110] Example 6
[0111] A method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical preparation, comprising the following steps:
[0112] S2, dissolving BFDO monomer in a mixed solvent of DMSO and propionic anhydride (the volume ratio of DMSO to propionic anhydride is 95:5) to obtain a solution with a BFDO monomer concentration of 10 mg / mL, adding 0.1 mol / L of lithium bis(trifluoromethanesulfonyl)imide to obtain an electrolyte;
[0113] S3, adding the conductive film substrate D3 into the electrolyte, using D3 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, using a three-electrode system and a constant voltage method to perform electrochemical polymerization, the potential relative to the reference electrode is 2.0 V, the time is 40 min, after the polymerization reaction, the working electrode is taken out, and vacuum dried at 80° C. for 60 min to obtain an electrochemically polymerized film M6;
[0114] S4. Add the electrochemically polymerized film M6 into the electrolyte, use M6 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, and use a three-electrode system and constant voltage method to carry out reduction doping treatment. The potential is -0.5 V relative to the reference electrode, and the time is 2 minutes. After the reaction, take out the working electrode, and dry it at 80°C in vacuum for 20 minutes to obtain the final conductive film M6-1.
[0115] Example 7
[0116] A method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical preparation, comprising the following steps:
[0117] S2, dissolving the BFDO monomer in a mixed solvent of DMSO and propionic anhydride (the volume ratio of DMSO to propionic anhydride is 95:5) to obtain an electrolyte with a BFDO monomer concentration of 10 mg / mL;
[0118] S3, adding the conductive film substrate D3 into the electrolyte, using D3 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, using a three-electrode system and a constant voltage method to perform electrochemical polymerization, the potential relative to the reference electrode is 2.2 V, the time is 60 min, after the polymerization reaction, the working electrode is taken out, and vacuum dried at 80° C. for 20 min to obtain an electrochemically polymerized film M7;
[0119] S4. Add the electrochemically polymerized film M7 into the electrolyte, use M7 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, and use a three-electrode system and constant voltage method to carry out reduction doping treatment. The potential is -0.5 V relative to the reference electrode, and the time is 3 minutes. After the reaction, take out the working electrode, and dry it at 80°C in vacuum for 20 minutes to obtain the final conductive film M7-1.
[0120] Example 8
[0121] A method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical preparation, comprising the following steps:
[0122] S2, dissolving BFDO monomer in a mixed solution of DMSO and propionic anhydride (the volume ratio of DMSO to propionic anhydride is 93:7) to obtain a solution with a BFDO monomer concentration of 10 mg / mL, adding 0.1 mol / L of lithium bis(trifluoromethanesulfonyl)imide to obtain an electrolyte;
[0123] S3, add the conductive film substrate D3 into the electrolyte, use D3 as the working electrode, platinum wire as the counter electrode, saturated calomel electrode as the reference electrode, adopt the three-electrode system and constant current method to carry out electrochemical polymerization, the current density is 0.50mA / cm 2 , the time is 70min, after the polymerization reaction, the working electrode is taken out and dried at 80℃ in vacuum for 20min to obtain the electrochemical polymerization treated film M8;
[0124] S4. Add the electrochemically polymerized film M8 into the electrolyte, use M8 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode, and use a three-electrode system and constant current method to perform reduction doping treatment. The reduction current density is 0.1 mA / cm 2, time is 2 minutes, after the reaction, take out the working electrode, vacuum dry at 80℃ for 20 minutes, and obtain the final conductive film M8-1.
[0125] Example 9
[0126] A method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical preparation, comprising the following steps:
[0127] S2, dissolving BFDO monomer in a mixed solution of DMSO and propionic anhydride (the volume ratio of DMSO to propionic anhydride is 9:1) to obtain a solution with a BFDO monomer concentration of 10 mg / mL, adding 0.1 mol / L tetrabutylammonium hexafluorophosphonate to obtain an electrolyte;
[0128] S3. Add the conductive film substrate D4 into the electrolyte, use D4 as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode. Use a three-electrode system and cyclic voltammetry to carry out electrochemical polymerization and reduction doping. The oxidation potential is 2.0V, the reduction potential is -0.6V, and the time is 80min. After the polymerization reaction, take out the working electrode, dry it at 80℃ in vacuum for 20min, and obtain the final conductive film M9-1.
[0129] Test Example 1
[0130] The electrical conductivity of the films prepared in Preparation Examples 1 to 6 and Examples 1 to 9 was tested; SEM images of the M1-1, M3-1, M5-1, M7-1, and M9-1 films prepared in Preparation Examples 1, 3, 5, and Examples 1 to 9.
[0131] The conductivity is calculated from the four-probe test and the film thickness test.
[0132] Test Results
[0133] Figure 1 The SEM images of the films prepared in Preparation Examples 1, 3, and 5 are shown. Figure 2 SEM images of the M1-1, M3-1, M5-1, M7-1, and M9-1 films prepared in Examples 1 to 9 are shown; Table 1 shows the electrical conductivity of the films prepared in Preparation Examples 1 to 6, and Table 2 shows the electrical conductivity of the films prepared in Examples 1 to 9.
[0134] Table 1 Electrical conductivity of the films prepared in Preparation Examples 1 to 6
[0135]
[0136] Table 2 Conductivity of the films prepared in Examples 1 to 9
[0137]
[0138]
[0139] Depend on Figure 1 , Figure 2 It can be seen that compared with the conductive film obtained in the preparation example, the conductive film obtained by the embodiment has a significantly smoother and tighter morphology structure, which is beneficial to improving the compactness, stability and conductivity of the n-type conductive polymer PBFDO film or BFDO film.
[0140] It can be seen from Table 1 and Table 2 that the conductivity of Preparation Examples 1 and 5 is significantly higher than that of other Preparation Examples, among which Preparation Example 1 is the highest, exceeding 2000S / cm. This is because Preparation Examples 1 and 5 use PBFDO polymer solutions with large molecular weight, high degree of polymerization and doping degree; Preparation Example 5 may cause the PBFDO film to become loose due to secondary immersion in DMSO solution, resulting in a decrease in conductivity compared with Preparation Example 1, which also reflects that the density of the film is crucial to the conductivity; the reason why the conductivity of Example 1 is significantly higher than that of other embodiments is consistent with the reason why the conductivity of Preparation Example 1 is the highest; the conductivity of the prepared embodiments is significantly improved compared with the corresponding preparation examples, because after electrochemical polymerization, the density and flatness of the film are greatly improved, especially after reduction doping, the doping degree of the film is further improved, and the conductivity is also further improved.
[0141] Test Example 2
[0142] The doped films prepared in Preparation Examples 1 to 6 and Examples 1 to 9 were used as cathodes to prepare organic solar cells and organic photodetection devices, and relevant device performance curves were obtained.
[0143] Test method:
[0144] The device structure of the organic solar cell is: silver (Ag) / molybdenum trioxide (MoO3) / active layer / cathode prepared in the preparation example or embodiment of the present invention and the substrate used, the active layer is a bulk heterojunction structure, including but not limited to polymer donor D18 and polymer acceptor PY-IT. The materials, preparation and testing methods are all conventional methods well known to practitioners in the organic solar cell industry.
[0145] The device structure of the organic photodetector is: silver (Ag) / molybdenum trioxide (MoO3) / active layer / cathode prepared in the preparation example or embodiment of the present invention and the substrate used, the active layer is a bulk heterojunction structure, including a polymer donor PTB7-Th and a non-fullerene acceptor COTIC-4F. The materials, preparation and testing methods are all conventional methods well known to practitioners in the organic photodetection industry.
[0146] Test Results
[0147] Table 3 shows the performance test results of organic solar cells based on the films prepared in Preparation Examples 1 to 6, Table 4 shows the performance test results of organic solar cells based on the doped films prepared in Examples 1 to 9, Table 5 shows the performance test results of organic photodetectors based on the films prepared in Preparation Examples 1 to 6, and Table 6 shows the performance test results of organic photodetectors based on the doped films prepared in Examples 1 to 9.
[0148] Figure 3 The JV curves of organic solar cells based on the thin films prepared in Preparation Examples 1 to 6 are shown;
[0149] in,
[0150] Figure 3 (a) is the JV curve of the organic solar cell based on the thin films prepared in Preparation Examples 1 to 3,
[0151] Figure 3 (b) is the JV curve of the organic solar cell based on the thin films prepared in Preparation Examples 4 to 6.
[0152] Figure 4 The JV curves of organic solar cells based on the doped thin films prepared in Examples 1 to 9 are shown;
[0153] in,
[0154] Figure 4 (a) is the JV curve of the organic solar cell based on the doped thin film prepared in Examples 1 to 3,
[0155] Figure 4 (b) is the JV curve of the organic solar cell based on the doped thin film prepared in Examples 4 to 6,
[0156] Figure 4 (c) is the JV curve of the organic solar cell based on the doped thin film prepared in Examples 7 to 9.
[0157] Figure 5 The dark current density (J) of the organic photodetector based on the thin films prepared in Preparation Examples 1 to 6 is shown. d ) and external quantum efficiency (EQE) curves;
[0158] in,
[0159] Figure 5 (a) is the dark current density (J) of the organic photodetector based on the thin films prepared in Preparation Examples 1 to 3 d )curve,
[0160] Figure 5 (b) is an external quantum efficiency (EQE) curve of an organic photodetector based on the thin films prepared in Preparation Examples 1 to 3,
[0161] Figure 5 (c) is the dark current density (J) of the organic photodetector based on the thin films prepared in Preparation Examples 4 to 6 d )curve,
[0162] Figure 5 (d) is the external quantum efficiency (EQE) curve of the organic photodetector based on the thin films prepared in Preparation Examples 4 to 6.
[0163] Figure 6 The dark current density (J) of the organic photodetector based on the doped thin films prepared in Examples 1 to 9 is shown. d ) and external quantum efficiency (EQE) curves;
[0164] in,
[0165] Figure 6 (a) is the dark current density (J) of the organic photodetector after doping of the thin film prepared in Examples 1 to 3 d )curve,
[0166] Figure 6 (b) is an external quantum efficiency (EQE) curve of an organic photodetector based on the doped thin film prepared in Examples 1 to 3,
[0167] Figure 6 (c) is the dark current density (J) of the organic photodetector based on the doped thin films prepared in Examples 4 to 6 d )curve,
[0168] Figure 6 (d) is an external quantum efficiency (EQE) curve of an organic photodetector based on the doped thin film prepared in Examples 4 to 6,
[0169] Figure 6 (e) is the dark current density (J) of the organic photodetector based on the doped thin films prepared in Examples 7 to 9 d )curve,
[0170] Figure 6 (f) is the external quantum efficiency (EQE) curve of the organic photodetector based on the doped thin films prepared in Examples 7 to 9.
[0171] Table 3 Performance test results of organic solar cells based on the films prepared in Preparation Examples 1 to 6
[0172]
[0173]
[0174] Table 4 Performance test results of organic solar cells based on the doped thin films prepared in Examples 1 to 9
[0175]
[0176] Table 5 Performance test results of organic photodetectors based on the films prepared in Preparation Examples 1 to 6
[0177]
[0178] Table 6 Performance test results of organic photodetectors based on the doped films prepared in Examples 1 to 9
[0179]
[0180] Depend on Figure 3 , Figure 4 It can be seen from Table 3 and Table 4 that the organic solar cells based on the doped thin films prepared in Preparation Examples 1 to 6 and Examples 1 to 9 have good photoelectric conversion efficiency, and packaging and storage for a period of time have little effect on the photoelectric conversion efficiency.
[0181] Depend on Figure 5 , Figure 6 As can be seen from Table 5 and Table 6, the organic photodetectors based on the doped thin films prepared in Preparation Examples 1 to 6 and Examples 1 to 9 have good performance. When the voltage is -2 V, the dark current density of the organic photodetectors in the examples is as low as about 5×10 -7 A / cm 2 The level of dark current is about , the lower the dark current density, the higher the detection sensitivity, which shows that the embodiment has good sensitivity; the 1050nm external quantum efficiency (EQE) of the embodiment can reach up to 46.5%, and the packaging and storage for 100 days has little effect on the 1050nm external quantum efficiency of the embodiment, which shows that the embodiment has a high efficiency in converting photons into electrical energy or light energy.
[0182] Test Example 3
[0183] The bending stability test was performed on the organic solar cell and organic photodetector based on the doped flexible film prepared in Preparation Example 4 and Example 9.
[0184] Test method:
[0185] The device structure of the organic solar cell is: silver (Ag) / molybdenum trioxide (MoO3) / active layer / cathode prepared in the preparation example or embodiment of the present invention and the substrate used, the active layer is a bulk heterojunction structure, including but not limited to polymer donor D18 and polymer acceptor PY-IT. The materials, preparation and testing methods are all conventional methods well known to practitioners in the organic solar cell industry.
[0186] The device structure of the organic photodetector is: silver (Ag) / molybdenum trioxide (MoO3) / active layer / cathode prepared in the preparation example or embodiment of the present invention and the substrate used, the active layer is a bulk heterojunction structure, including a polymer donor PTB7-Th and a non-fullerene acceptor COTIC-4F. The materials, preparation and testing methods are all conventional methods well known to practitioners in the organic photodetection industry.
[0187] Test Results
[0188] Table 7 shows the bending stability test results of the doped flexible films prepared in Preparation Example 4 and Example 9 and their organic solar cells and organic photodetectors.
[0189] Table 7 Bending stability test results of the doped flexible films prepared in Preparation Example 4 and Example 9 and their organic solar cells and organic photodetectors
[0190]
[0191]
[0192] It can be seen from Table 7 that after Preparation Example 4 was bent 500 times, the conductivity, organic solar cell device conversion efficiency PCE, and organic photodetector external quantum efficiency all decreased significantly, while Example M9-1 only decreased slightly, indicating that the bending stability of Example M9-1 is significantly better than that of Preparation Example 4.
[0193] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0194] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a high-density electron transport electrode film on a non-conductive substrate by electrochemical preparation, characterized in that: The method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical means comprises the following steps: S1, placing an oxidant, 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione and / or poly(3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione) on a substrate to obtain a conductive film substrate layer; S2, mixing 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione, a solvent, and an acid anhydride to obtain an electrolyte; S3, adding the conductive film substrate layer described in S1 into an electrolyte, and performing electrochemical polymerization using three electrodes to obtain an electrochemically polymerized film I.
2. The method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical method according to claim 1, characterized in that: The method for preparing a high-density electron transport type electrode film on a non-conductive substrate by electrochemical means further comprises the following steps: S4. Using a three-electrode system, the electrochemically polymerized film I is subjected to reduction doping treatment to obtain a final conductive film II.
3. The method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical method according to claim 1, characterized in that: In step S1, the oxidant, 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione and / or poly(3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione) are disposed on the substrate: The oxidant and 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione are placed on the surface of the substrate, and after heating and drying, the process is repeated n times to obtain a conductive film substrate layer; or The poly (3,7-dihydrobenzo [1,2-b: 4,5-b'] difuran-2,6-dione) is disposed on the surface of the substrate, and after heating and drying, a conductive film substrate layer is obtained; The n is 1-20.
4. The method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical method according to claim 3, characterized in that: The method of setting on the surface of the substrate adopts a dipping method or a coating method.
5. The method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical method according to claim 1, characterized in that: In step S2, the solvent is selected from one or more polar aprotic solvents.
6. The method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical method according to claim 1, characterized in that: In step S3, in the three-electrode system, the conductive film substrate obtained in step S1 is used as the working electrode, the platinum wire is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode.
7. The method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical method according to claim 1, characterized in that: In step S3, the electrochemical polymerization is carried out by constant current method, constant voltage method or cyclic voltammetry method, and the potential relative to the reference electrode is -1.5 to 3.0 V or the current density is 0.001 to 500 mA / cm 2 , the polymerization time is 20 to 200 minutes or 20 to 2000 cycles.
8. The method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical method according to claim 7, characterized in that: The cyclic voltammetry method can simultaneously perform electrochemical polymerization and reduction doping treatment.
9. The method for preparing a high-density electron transport type electrode thin film on a non-conductive substrate by electrochemical method according to claim 2, characterized in that: In step S4, the reduction doping is carried out by constant current method or constant voltage method, and the reduction potential is -1.5 to 0.5 V relative to the reference electrode or the reduction current density is 0.001 to 100 mA / cm 2 , time is 1 to 10 minutes.
10. Application of the high-density electron transport electrode film prepared by electrochemistry on a non-conductive substrate as claimed in any one of claims 1 to 9 in organic electronic devices.
Citation Information
Patent Citations
Organic field effect transistor and preparation method thereof
CN103594624A
Method for preparing cathode of solid electrolytic capacitor by in-situ polymerization method
CN116825545A
Synthesis of a water-based p-type donor polymer
WO2024165176A1
Cited By
Flexible electrode for electronic skin and preparation method thereof
CN121483706A